Evaluasi Sistem Pengendalian Intern Pemberian Pinjaman Anggota Pada Unit Simpan Pinjam Koperasi Peternak Sapi Bandung Utara Lembang - Yuni Kusumawati; Yanti Rufaedah (Indonesian Accounting Literacy Journal, 2021)
This study aims to evaluate the internal control system for providing member loans at Simpan Pinjam Unit of Koperasi Peternak Sapi Bandung Utara Lembang. The research method used is descriptive qualitative analysis method with data analysis tool in the form of control matrix. The technique used in data collection is interviews and documentation, and is strengthened by a questionnaire containing questions that refer to the internal control component according to COSO. The results showed that the implementation of the internal control system for providing member loans at Simpan Pinjam Unit of Koperasi Peternak Sapi Bandung Utara Lembang, had fulfilled the internal control objectives based on COSO but was still not optimal because there were several control elements that had not been implemented which had a significant impact, namely elements on the environmental control component, risk assessment, and control activities.